PELATIHAN STATISTIKA DASAR UNTUK GURU PENDAMPING PENELITIAN SISWA SMA/SEDERAJAT - Wutsqa, Dhoriva Urwatul; Insani, Nur; Setiawan, Ezra Putranda; Nur'aini, Rizky; Arini, Luthfia Hanun Yuli (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
This training activity is part of the Lecturers’ Off-Campus Engagement Program organized by the Statistics Study Program, Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta (UNY) in collaboration with the Research Mentor Teachers Association (Musyawarah Guru Pembimbing Penelitian, MGPP) of the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta, DIY). The training was motivated by the need for senior high school research mentor teachers to possess fundamental statistical skills to guide students in conducting quantitative research. The activity was carried out as a one-day training consisting of three main sessions: data visualization, data analysis, and data collecting and processing. The training method combined theoretical explanations and practical exercises using Microsoft Excel. A total of 33 teachers from various disciplines enthusiastically participated in the program. Evaluation results indicated that the training was effective and achieved a high level of participant satisfaction. Participants also demonstrated significant improvement in their ability to select appropriate data visualizations, understand sampling concepts, perform descriptive analysis and basic statistical tests, and enhance their confidence in supervising student research. The success of this program was supported by strong collaboration between the UNY Statistics lecturers and MGPP DIY. Nevertheless, the limited training duration was identified as a primary constraint, suggesting the need for follow-up activities with more extensive practical sessions. Overall, this training effectively enhanced teachers’ competence in basic statistics and strengthened the synergy between universities and schools in fostering a research culture within secondary education.